Muhammad Iqbal (Sejarah dan Pemikiran Teologisnya) - Mansur, Rosichin (STAI Miftahul Ula Nganjuk, 2015)
Abstract: Muhammad Iqbal is actually more famous as an existentialist philosopher. Therefore, it is rather difficult to find views on the discourse of classical theology, as a function of reason and revelation, acts of God, human actions and obligations of God. That does not mean that he did not alluded to theology. Humans live to know his personality and strengthen and develop their talents, not the reverse, namely personal weaken, as practiced by the Sufis who beat so mortal soul with Allah. In essence denying the self is not the teachings of Islam because the nature of life is movement, and movement is change. Iqbal outlook on life equilbirium between morality and religion; ethics and politics; ritual and worldly, is actually not new in Islamic thought. However, in the course of history, thus buried with the current thinking of Muslim political life are getting worse, especially since the collapse and destruction of Baghdad, in 1258.